2012
DOI: 10.1111/j.1469-8749.2012.04393.x
|View full text |Cite
|
Sign up to set email alerts
|

Generic patient‐reported outcomes in child health research: a review of conceptual content using World Health Organization definitions

Abstract: AIM Our aims were to (1) describe the conceptual basis of popular generic instruments according to World Health Organization (WHO) definitions of functioning, disability, and health (FDH), and quality of life (QOL) with health-related quality of life (HRQOL) as a subcomponent of QOL; (2) map the instruments to the International Classification of Functioning, Disability and Health (ICF); and (3) provide information on how the analyzed instruments were used in the literature. This should enable users to make val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
138
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(143 citation statements)
references
References 36 publications
2
138
0
3
Order By: Relevance
“…The use of a common framework to describe content has proven to be advantageous [82]. We reviewed the content of the items and constructs assessed by the questionnaires using methods similar to those used by other authors [83,84]. We used an independent checking method for quality assuring the mapping process as a proportionate use of resources.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a common framework to describe content has proven to be advantageous [82]. We reviewed the content of the items and constructs assessed by the questionnaires using methods similar to those used by other authors [83,84]. We used an independent checking method for quality assuring the mapping process as a proportionate use of resources.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO defines quality of life (QOL) as ‘a child's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns’1 and HRQOL) as ‘a child's goals, expectations, standards or concerns about their overall health and health-related domains’ 1 2. That being said, many other definitions of HRQOL have been proposed over the years, and a variety of terms are currently used 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…For an overview of the most commonly used generic HRQOL questionnaires in paediatrics, see table 1. This table is based on a combination of questionnaires named in three review manuscripts written by paediatric HRQOL researchers 2 3 27. Based on two of the three reviews, the PedsQL 4.0 generic scale is mentioned as the most frequently used questionnaire in paediatric HRQOL research.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of QOL measures found that only half of the available child epilepsy-specific measures provided options for child self-report, 5 and use of child report of QOL was not dominant in child health services research in general. 6 A dependence on parental report to assess child QOL represents a limitation for both substantive and empirical reasons. The World Health Organization defines QOL as "an individual's perception of [his/her] position in life .…”
mentioning
confidence: 99%